УМУМИЙ ЎРТА ТАЪЛИМ МАКТАБЛАРИ ЎҚУВЧИЛАРИГА МИЛЛИЙ ҲУНАРМАНДЧИЛИКНИ ЎРГАТИШНИНГ ТАРБИЯВИЙ ИМКОНИЯТЛАРИ - Айтмуратов, Б.Т. (SCIENCE and SOCIETY, 2022)
This article researches about the psychological and pedagogical potential of secondary schools learners in search of handicraft through the prism of didactic principles, requirements and measures.